Esgotamento do padrão de acumulação de capital e política econômica brasileira: do II PND aos anos 2000 - Gerioni, Enzo Matono (2014)
This work aim to show that the reach to the limits of capital accumulation, which is showing its first signs since the 60 s, has and still is exercising great importance in Brazilian economic policies. In the first chapter, we establish a reference to what is understood as the limit of capital accumulation after World War II and how the accumulation process drives itself to its own limits. In the following chapters, we detach the importance of the reached limit to the most relevant moments of Brazilian economic policy. Since the IIPND, when the first signs of influence raise in Brazilian economy, passing through the stabilizing attempts during the 80 s and 90 s and the emergence of the pro-market State in Brazil, until the 00 s, when macroeconomic prudence took shape and delimited the conduction of the country s economic policy, we will show how the limit of capital accumulation has played an important role.